TESTS AS A MEANS OF OBJECTIVE DIAGNOSIS OF THE KNOWLEDGE QUALITY IN THE CONTEXT OF IMPLEMENTATION OF PROBLEMATIC TEACHING FOR CLINICAL CYCLE DISCIPLINES IN A VETERINARY INSTITUTION - O E Davydova; N V Pimenov (Universitas Brawijaya, 2018)
The principle of problem characterizes the features of an objective assessment of the quality of education in the fileld of